7 - Patrick Bond. Cities of Gold, Townships of Coal: Essays on South Africa’s New Urban Crisis. Trenton and Asmara: Africa World Press, Inc. 2000. - Caroline O'Reilly; Geoffrey Wood (African Sociological Review, 2000)
Abstract